In vitro antioxidant activities of the novel pentapeptides Ser‐His‐Glu‐Cys‐Asn and Leu‐Pro‐Phe‐Ala‐Met and the relationship between activity and peptide secondary structure. (3rd October 2016) - Yang, Ruiwen; Wang, Jia; Lin, Songyi; Ye, Haiqing; Chen, Feng
Abstract: BACKGROUND: Using high‐performance liquid chromatography/tandem mass spectrometry, two novel antioxidant pentapeptides [Ser‐His‐Glu‐Cys‐Asn (SHECN) and Leu‐Pro‐Phe‐Ala‐Met (LPFAM)] were identified from 1–3‐kDa soybean protein hydrolysates (SPH). The MTT [3‐(4, 5‐dimethylthiazol‐2‐yl)‐2, 5‐diphenyltetrazolium bromide] assay was used to evaluate cytotoxicity in HepG2 cells. Antioxidant activity was measured using in vitro assays, including the cellular antioxidant activity assay (CAA), 2, 2‐diphenyl‐1‐picrylhydrazyl or 2, 2‐azino‐bis(3‐ethylbenzothiazoline‐6‐sulfonic acid) diammonium salt (ABTS) inhibition, and oxygen radical absorbance capacity (ORAC) assays. Finally, the secondary structure was determined using circular dichroism (CD). RESULTS: The results revealed that two novel peptides were nontoxic and possessed antioxidant activity. SHECN had significantly higher antioxidant activity than LPFAM ( P < 0.05). The CAA value of SHECN was 776.22 µmol QE 100 g −1 . SHECN also showed significant DPPH inhibition (70.18 ± 4.06%) and ABTS inhibition (88.16 ± 0.76%). It had normalized ORAC values of 0.3000 ± 0.0070 µmol GE mg −1 and 0.0900 ± 0.0020 µmol TE mg −1, respectively. The results of the CD analysis demonstrated that, compared to LPFAM, which had much lower antioxidant activity, SHECN had a high β‐sheet content and reduced α‐helix content. CONCLUSION: The results indicated that SHECN possessed high antioxidant activity. A higher β‐sheet content and lower content levels of α‐helix appear to be correlated with antioxidant activity. © 2016 Society of Chemical Industry